Synthesis of an inositol hexakisphosphate (IP6) affinity probe to study the interactome from a colon cancer cell line. Issue 3 (3rd February 2016) - Yin, Meng-xin; Catimel, Bruno; Gregory, Mark; Condron, Melanie; Kapp, Eugene; Holmes, Andrew B.; Burgess, Antony W.
Abstract : Inositol hexakisphosphate (InsP6 or IP6 ) is an important signalling molecule. An IP6 probe was synthesised from myo -inositol and immobilised onto Dynabeads for proteomic analysis. LC/MS/MS analysis identified 77 proteins or protein complexes that bind to IP6 specifically. Abstract : Inositol hexakisphosphate (InsP6 or IP6 ) is an important signalling molecule in vesicular trafficking, neurotransmission, immune responses, regulation of protein kinases and phosphatases, activation of ion channels, antioxidant functions and anticancer activities. An IP6 probe was synthesised from myo -inositol via a derivatised analogue, which was immobilised through a terminal amino group onto Dynabeads. Systematic analysis of the IP6 interactome has been performed using the IP6 affinity probe using cytosolic extracts from the LIM1215 colonic carcinoma cell line. LC/MS/MS analysis identified 77 proteins or protein complexes that bind to IP6 specifically, including AP-2 complex proteins and β-arrestins as well as a number of novel potential IP6 interacting proteins. Bioinformatic enrichment analysis of the IP6 interactome reinforced the concept that IP6 regulates a number of biological processes including cell cycle and division, signal transduction, intracellular protein transport, vesicle-mediated transport and RNA splicing.